Peningkatan Kemampuan Menulis Anak Usia Dini Dengan Menggunakan Metode Meniru Tulisan - Chairunnisa Chairunnisa (STIU Al-Mujtama Pamekasan, 2020)
Knowing the development of fine motoric skills through imitation activities in early childhood is the goal of the results of this classroom action research (PTK), through direct research with a sample of group B at PAUD ArRohman East Jakarta for the 2018/2019 academic year. The method used is the method of imitating writing, data collection techniques by observation and documentation. This research was conducted in 3 cycles in 3 days. The research consisted of 4 stages, namely: planning, acting, observing and reflecting. The first cycle is meeting. The comparative analysis technique is to compare the child's ability for each cycle, namely the percentage of success. The results of this study showed that there was an increase of 5% per cycle, namely the end of the results there were 37 students who experienced a significant increase in writing, compared to the initial observation, and only 17 students out of 40 were able to write. This shows that the fine motoric skills of children have increased through imitating writing activities. This can be seen from the percentage of the results of the observation of children's fine motoric skills. Keywords: Children's Fine Motoric, Writing Imitation Method, PTK.